FOREIGNIZING OR DOMESTICATING ENGLISH CHILDREN’S LITERATURE TRANSLATED INTO ARABIC: THE CASE OF ALICE’S ADVENTURES IN WONDERLAND - Mohannad Sayaheen; Tengku Sepora Tengku Mahadi; Bilal Sayaheen, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This study investigated two significant translation methods, namely foreignization and domestication, when translating children’s literature from English into Arabic. The purpose of the study is to find answers for two questions. First, do the norms regulate the translation of English children’s literature into Arabic. Second, to which method do translators opt for when translating English children’s literature into Arabic. The current paper attempts to identifying whether translating English children’s literature into Arabic is regulated by norms or not. The translator has one option when translating a text, either to domesticate or to foreignize the text based on Schleiermacher’s method of translation. Two translated versions of Alice’s Adventures in Wonderland were analysed at the level of diction and discourse. A descriptive analysis of the norms was used to analyse this study and specific theoretical frameworks were used by the researchers in order to classify the selected items. The classification included ten major categories proposed by Klingberg (1986). After spotting the selected items based on the mentioned theoretical framework, each item translated in both versions was classified based on the two main methods that consist the centre of the current study i.e., domestication and foreignization Pedersen (2005). The results of the analysis show that the translations of these two Arabic versions are not systematically regulated by norms; examples of both foreignization and domestication were found in both versions. However, the analysis shows that either domestication or foreignization is more prevalent in each version.